Peran Strategis Guru dalam Pembentukan Kepribadian Melalui Pembelajaran Pendidikan Agama Islam di SMA Nurul Jadid - Mubarak Marzuqi (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2024)
TARBAWI : Jurnal Studi Pendidikan Islami Vol 10 No 1 April 2022 https://doi.org/10.55757/tasharruf Received: date Accepted: date Published: date Publisher’s Note: Pusat Penelitian dan Pengembangan (P3M) Sekolah Tinggi Agama Islam Salahuddin (STAIS) Pasuruan, Indonesia stays neutral with regard to jurisdictional claims in published maps and institutional affiliations. Copyright: © 2023 by the authors. Submitted for possible open access publication under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by-sa/4.0). Abstract : The aim of preparing this work is the strategic role of teachers in personality formation through learning Islamic religious education at Nurul Jadid High School. The work was carried out using a qualitative case study method at Nurul Jadid High School, using participant observation techniques, semi-structured interviews with PAI teachers, and theme analysis and qualitative coding to identify relevant patterns and findings from the data collected. The result of this work is that the role of the Islamic Religious Education (PAI) teacher at Nurul Jadid High School is very vital in shaping students' personalities through Islamic religious learning. They become role models, guide understanding of moral values, and direct student behavior with an Islamic approach. A conducive learning environment and experience-based learning methods strengthen the process of internalizing religious values. Overall, PAI teachers play a role not only as teachers, but also as shapers of character who have integrity and are beneficial to society. The main difference of this work is that it focuses on Nurul Jadid High School, allowing for more in-depth research on the dynamics of PAI learning and the role of teachers in shaping students' personalities, as well as providing more contextual recommendations